(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The influence of the dopant on the regularity of the sol-gel synthesis of a gas-sensitive material based on tetraethoxysilane and metal oxides Ti and Cd in the presence of a template was studied. Analysis of the composition of the synthesized nanocomposites by DTA, XRD, and SEM showed that the elemental composition of HCM corresponds to the composition of the components used in their preparation. To obtain highly porous films, heat treatment of HCM at 400-450 0C is recommended. Samples of thin films of the TEOS/75TiO2+CdO composition, which are gas sensitive to CO, have been obtained. Selective sensors for carbon monoxide II based on the developed HCMs have been created and optimal conditions have been established that ensure the highest sensitivity and selectivity of the developed sensors.